Best Answer

x + 4 + 3x + 2

Before we jump into this confusing tangle of higher algebra and arithmetic,

let's put it aside for a minute, and work out a simpler problem, just to get

warmed up.

Try this one first:

1 cow + 4 + 3 cows + 2.

Add up the cows: 1 cow + 3 cows = 4 cows

Add up the numbers: 4 + 2 = 6

Put them back together: 4 cows + 6.

Now that we're warmed up, we can go back to the original problem in the question:

1x + 4 + 3x + 2

Add up the 'x's :1x + 3x = 4x

Add up the numbers: 4 + 2 = 6

Put them back together: 4x + 6

Q: How do you add x plus 4 plus 3x plus 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

It is: 3x^2 +15x +12

8x - 2x - 2 = 3x + 2x + 4 Combine like terms: 6x - 2 = 5x + 4 Subtract 5x from both sides: x - 2 = 4 Add 2 to both sides: x = 6

Let the symbol ^ mean "to the power" Then 9x^2 + 24x + 16 = (3x + 4)(3x +4) = (3x + 4)^2

(3x + 5)(3x^2 + 4)

x+7=3x+3 4=2x 4/2=2 x=2

Related questions

9x2 + 12x + 4 = 9x2 + 6x + 6x + 4 = 3x(3x + 2) + 2(3x + 2) = (3x + 2)(3x + 2) = (3x + 2)2

The sum of 3x plus 2 and -4 plus 3 is 3x+1 if the equation is (3x+2)+(-4+3). If they are two separate questions, 3x+2 remains as itself while -4+3=-1.

The equivalent expression of 3x-9 plus 3x plus 5 is negative 4.

2(3x + 4) + 5x - 2

It is: 3x^2 +15x +12

The equation can be simplified to show a value of Y in terms of X. 3X + 2Y +2 = 4Y + 4 3X + 2 = 2Y + 4 3X -2 = 2Y and 2Y = 3X - 2 means that Y = (3/2 X) -1

8x - 2x - 2 = 3x + 2x + 4 Combine like terms: 6x - 2 = 5x + 4 Subtract 5x from both sides: x - 2 = 4 Add 2 to both sides: x = 6

3x - 2 = 2x + 4 3x - 2x = 4 + 2 x = 6

3x + 2 = -10 3x = -12 x = -4

x = 7 and 2/3

Let the symbol ^ mean "to the power" Then 9x^2 + 24x + 16 = (3x + 4)(3x +4) = (3x + 4)^2

(3x + 5)(3x^2 + 4)